Vasoactive intestinal peptide-expressing interneurons are impaired in a mouse model of Dravet syndrome - Goff, Kevin M; Goldberg, Ethan M (eLife, 2019)
Dravet Syndrome (DS) is a severe neurodevelopmental disorder caused by pathogenic loss of function variants in the gene SCN1A which encodes the voltage gated sodium (Na+) channel subunit Nav1.1. GABAergic interneurons expressing parvalbumin (PV-INs) and somatostatin (SST-INs) exhibit impaired excitability in DS (Scn1a+/-) mice. However, the function of a third major class of interneurons in DS – those expressing vasoactive intestinal peptide (VIP-IN) –is unknown. We recorded VIP-INs in brain slices from Scn1a+/-mice and wild-type littermate controls and found prominent impairment of irregular spiking (IS), but not continuous adapting (CA) VIP-INs, in Scn1a+/- mice. Application of the Nav1.1-specific toxin Hm1a rescued the observed deficits. The IS vs. CA firing pattern is determined by expression of KCNQ channels; IS VIP-INs switched to tonic firing with both pharmacologic blockade of M-current and muscarinic acetylcholine receptor activation. These results show that VIP-INs express Nav1.1 and are dysfunctional in DS, which may contribute to DS pathogenesis.
Keywords: epilepsy; Nav1.1; SCN1A; electrophysiology; ion channels